2012
DOI: 10.5539/ijms.v4n3p134
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction Modeling in Hotel Industry: A Case Study of Kish Island in Iran

Abstract: Purpose-Hotel Industry is one of the most substantial factors for Tourism Industry. It could provide the necessary substructures for Tourism. Therefore the growth in Tourism industry depends on growth in Hotel industry. Hotel industry had a major growth in recent years in Iran; therefore the purpose of this paper is to explore the customer satisfaction in hotel industry. This paper aims to identify the relation between customer satisfactions as dependent variable with other independent variables such image, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
(25 reference statements)
3
35
0
4
Order By: Relevance
“…When the customer perception exceeds the customer expectation, customer satisfaction will occur [1]. Customer satisfaction plays an indispensable element of creating and maintaining the relationship between service providers and customers.…”
Section: B Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the customer perception exceeds the customer expectation, customer satisfaction will occur [1]. Customer satisfaction plays an indispensable element of creating and maintaining the relationship between service providers and customers.…”
Section: B Customer Satisfactionmentioning
confidence: 99%
“…Hospitality is known to be the one of the major factors that contribute to strengthen the business in many nations [1]. It is also one of the most developing industry that considerably impact on guests who desire to accommodate places in many beautiful places in the world.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that analyse the needs and desires of hotel guests, elucidating the relevance for guest satisfaction of a variety of attributes such as cleanliness, price, location, security, personal service, physical attractiveness, opportunities for relaxation, standard of services, appealing image, and reputation (Atkinsons, 1988;Cadotte and Turgeon, 1988;Knutson, 1988;Wilensky and Buttle, 1988;Rivers et al, 1991;Ananth et al, 1992;Barsky and Labagh, 1992;McCleary et al, 1993;Saeed et al, 2011;Mohajerani and Miremadi, 2012). Wuest et al (1996) defined the perception of hotel attributes as the degree to which guests may find various services and facilities critical to their stay in the hotel.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Smith (1995) further stated that "value is perceived when customers' requirements are met at an attractive price". Mohajerani and Miremadi (2012) have shown that the higher the perceived value, the more satisfied the customer is. The findings revealed that the hospitality guest considered value to be more important than the price.…”
Section: Wwwccsenetorg/ijmsmentioning
confidence: 99%
“…Ferrel and Hartline (2010) also established that perceived value is an output of customer benefits and costs. Woodall (2003) as quoted by Mohajerani and Miremadi (2012) described this value as "the personal perception of advantage arising out of customer associated with the offering of an organization". Smith (1995) further stated that "value is perceived when customers' requirements are met at an attractive price".…”
Section: Wwwccsenetorg/ijmsmentioning
confidence: 99%